Physics Teachers’ Perceptions of Senior High Schools in Merauke on Self-Regulation of Digital Instructional Materials - Andi Reski; Tutik Yuliatun; Nurlayli Hasanah; Desy Kumala Sari (Universitas Lambung Mangkurat, 2023)
This study describes the high school and MA physics teachers' perceptions of the need for digital teaching materials like e-modules, e-student worksheets, e-comics, and learning videos. The type of research used is descriptive quantitative. Therefore, as many as 12 physics teachers from SMA and MA in Merauke City were sampled in the study. The sample in this study was selected through a purposive sampling technique with criteria based on educational strata, length of teaching, educator certificate and ease of access. Furthermore, data collection was carried out using an instrument in the form of a questionnaire containing 30 statement items with a Likert scale consisting of 5 answer choices. Then, data analysis uses descriptive statistics. The result of this analysis is the accumulation of basic data in the form of the percentage of total responses followed by determining response criteria using interpretation criteria. Based on these criteria, it can be seen that the criteria for physics teachers' perceptions of the need for digital teaching materials. The study results show that the average perception of physics teachers is 88.1% and is included in the criteria for needing digital teaching materials. According to the teacher's perception, the order of priority for teaching material needs is e-module with the TPACK approach (91.3%), e-student worksheets with a scientific approach (83.3%), and interactive multimedia-based learning videos (75%). This research collected data on the perceptions of physics teachers at SMA and MA Merauke as a stage of needs analysis in development research. Based on the results of this analysis, further research will be carried out regarding the development of digital teaching materials in the form of e-modules, e-student worksheets, and learning videos.